2003
DOI: 10.1136/adc.88.6.529
|View full text |Cite
|
Sign up to set email alerts
|

Systemic neutrophil activation in acute preschool viral wheeze

Abstract: Background: In preschool children, attacks of wheeze are usually triggered by viral colds. The inflammatory substrate in preschool viral wheeze (PVW) is unclear, but epidemiological data suggest that most PVW is not caused by allergic inflammation. We therefore speculated that the neutrophils are an important effector cell. Systemic neutrophil activation is the first stage for the development of pulmonary neutrophilia. Markers of neutrophil activation are shedding of the adhesion molecule L-selectin from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 23 publications
3
14
0
2
Order By: Relevance
“…Infants in the present study were from an unselected population and maternal atopy did not modify any of the associations found, which may explain the discrepancies. Although there is evidence that most asthma starts early in life [23], respiratory morbidity in the preschool child is mostly related to neutrophilic airway inflammation [24] and there is very little evidence of chronic eosinophilic bronchial inflammation in the first months of life [25].…”
Section: Discussionmentioning
confidence: 99%
“…Infants in the present study were from an unselected population and maternal atopy did not modify any of the associations found, which may explain the discrepancies. Although there is evidence that most asthma starts early in life [23], respiratory morbidity in the preschool child is mostly related to neutrophilic airway inflammation [24] and there is very little evidence of chronic eosinophilic bronchial inflammation in the first months of life [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that there will be considerable overlap in these relationships between different clinical syndromes, as reviewed by Wenzel 55. An example where childhood and adult phenotypes might overlap is evidenced by the few opportunistic studies of viral-associated wheeze in young children that have demonstrated predominantly neutrophil- as opposed to eosinophil-mediated airway inflammation 56 57. These results suggest the presence of different pathological phenotypes of wheezing illness in young children and also hint at similarities with adult classifications of non-eosinophilic airway inflammation 38…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…Studies in infants found that FeNO was positively associated with recurrent wheezing [3][4][5], whereas lower FeNO was associated with virus-associated wheezing [6] and with upper and lower respiratory symptoms [7,8]. Indeed, respiratory morbidity in infants is mostly related to neutrophilic airway inflammation, which does not increase FeNO [9], and not to eosinophilic inflammation [10,11]. Previous studies in young children are difficult to compare as different inclusion criteria and methods of measuring FeNO have been used.…”
mentioning
confidence: 98%